Review on foreground artificial intelligence in games - Ganguly, Rajjeshwar; Rithvik Reddy, Dubba; Venkataraman, Revathi; S, Sharanya (International Journal of Engineering and Technology, 2018)
Artificial Intelligence (AI) is applied in almost every field existing in today's world and video games prove to be an excellent ground due to its responsive and intelligent behaviour. The games can be put to use model human- level AI, machine learning and scripting behaviour. This work deals with AI used in games to create more complicated and human like behaviour in the non player characters. Unlike most commercial games, games involving AI don’t use the AI in the background rather it is used in the foreground to enhance player experience. An analysis of use of the AI in a number of existing games is made to identify patterns for AI in games which include decision trees, scripted behaviour and learning agents.
Keywords: Artificial Intelligence (AI); Foreground AI (F-AI); Non Playable Character (NPC); First Person Shooter (FPS); Reinforcement Learning (RL).